Potensi Pengembangan Destinasi Pariwisata Super Prioritas di Kawasan Ekonomi Khusus Likupang - Maria Heny Pratiknjo; Femmy Tulusan; Deysi L. N. Tampongangoy (Lembaga Bale Literasi, 2025)
This study examine the potential and challenges of developing the Likupang Special Economic Zone (SEZ) through a social anthropological approach, with an emphasis on the dynamics of identity, social relations, and the cultural capital of the local community. This study adopts a qualitative interpretive case study, employing participant observation, in-depth interviews, and document analysis in villages surrounding the Likupang Special Economic Zone (SEZ), namely Marinsow, Pulisan, and Kinunang. Data were analyzed thematically and interpretatively using a social anthropological perspective, drawing on Bourdieu’s (1986) concepts of social and symbolic capital, MacCannell’s theory of cultural commodification, and Appadurai’s (1996) framework on cultural globalization. The findings reveal that local cultural practices such as the Foso Rumagesa ritual and the mapalus value hold significant potential as symbolic capital and tourist attractions. However, the process of cultural commodification and the influx of large-scale investment have led to social fragmentation, unequal access, and value transformations that threaten the sustainability of the community’s cultural identity. Additionally, social relations have shifted due to an imbalance between local and external actors, along with a lack of meaningful community participation in decision-making. This study emphasizes that the success of the Likupang SEZ development is highly dependent on the implementation of an inclusive, community-based tourism model. Key recommendations are to build local community capacity, safeguard cultural expression, conduct socio-cultural impact assessments, and promote fair partnerships among government, private sector, and communities. A social anthropological approach is essential for developing tourism strategies attuned to local social and cultural contexts.